2021
DOI: 10.17762/turcomat.v12i3.1018
|View full text |Cite
|
Sign up to set email alerts
|

Dimensioning UX Models for Design and Evaluation

Abstract: This paper attemptsto find out the available dimensions of user experience models in extant literature. The study observed that there are numeroususer experience models with a number of dimensions. This notwithstanding, there appears to be no concordamong practitioners and researchers on the dimensioning of UX models. The reason for lack of consensus is due tounderlying nature of user experience which signifies that UX should be structured and dimensioned differently dependent on the context and domain of use.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, the corresponding contributions are dated or incapable of addressing the limitation towards a concrete direction, as pointed out in Section 2. The need for a holistic and comprehensive analysis of UX is particularly stressed by Hussain et al [17], who identified a set of dimensions related to digital and interactive system design. However, these dimensions alone are not sufficient to provide a complete picture of UX since the fundamental elements of UX, influence factors and their impact on the interaction outputs, are not provided.…”
Section: Discussionmentioning
confidence: 99%
“…However, the corresponding contributions are dated or incapable of addressing the limitation towards a concrete direction, as pointed out in Section 2. The need for a holistic and comprehensive analysis of UX is particularly stressed by Hussain et al [17], who identified a set of dimensions related to digital and interactive system design. However, these dimensions alone are not sufficient to provide a complete picture of UX since the fundamental elements of UX, influence factors and their impact on the interaction outputs, are not provided.…”
Section: Discussionmentioning
confidence: 99%
“…This unclarity affects studies and contributions aiming at analysing UX from a theoretical perspective. A considerable shortcoming is the frequent failure to analyse the holistic quality of UX (Satti et al 2019; Hussain, Mkpojiogu, & Husin 2021). In other words, scholars recognise the complexity and multifaceted nature of UX, but then they tend to focus on a few particular elements only (Berni & Borgianni 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, scholars recognise the complexity and multifaceted nature of UX, but then they tend to focus on a few particular elements only (Berni & Borgianni 2021a). Such elements are identified but seldom studied comprehensively (Hussain, Mkpojiogu, & Husin 2021).…”
Section: Introductionmentioning
confidence: 99%